2012
DOI: 10.15760/comminfolit.2012.6.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy on the Web: How College Students Use Visual and Textual Cues to Assess Credibility on Health Websites

Abstract: One of the most important literacy skills in today's information society is the ability to determine the credibility of online information. Users sort through a staggering number of websites while discerning which will provide satisfactory information. In this study, 70 college students assessed the credibility of health websites with a low and high design quality in either low or high credibility groups. The study's purpose was to understand if students relied more on textual or visual cues in determining cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Studies have shown strong support for the claim of individuals' media perceptions affecting their information processing, such as the scholarship on source credibility (Petty & Cacioppo, 1984;Trumbo & McComas, 2003;Pareira, 2012). Petty and Cacioppo (1984) suggested that perceptions such as source credibility could guide one's information processing path.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown strong support for the claim of individuals' media perceptions affecting their information processing, such as the scholarship on source credibility (Petty & Cacioppo, 1984;Trumbo & McComas, 2003;Pareira, 2012). Petty and Cacioppo (1984) suggested that perceptions such as source credibility could guide one's information processing path.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An empirical study conducted by Trumbo and McComas (2003) found that high credibility tends to promote heuristic processing while low credibility promotes greater systematic processing. More recently, Pareira (2012) found that the information processing path triggered by one's media perception influences the quality of cognitive outcome. In an experiment, students were able to recall content better from websites they deemed as highly credible compared to those that were not (Pareira, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudios han encontrado fuerte evidencia de que las percepciones que los individuos tienen de los medios de comunicación afectan el procesamiento de la información, como los estudios en la credibilidad de la fuente (Petty y Cacioppo, 1984;Trumbo y McComas, 2003;Pareira, 2012). Petty y Cacioppo (1984) sugieren que las percepciones como la credibilidad de la fuente podrían guiar la ruta de procesamiento de información.…”
Section: Revisión De La Literaturaunclassified
“…Más recientemente, Pareira (2012) encontró que la ruta de procesamiento de información provocada por la percepción de los medios de comunicación influye en la calidad del resultado cognitivo. En un experimento, los estudiantes fueron capaces de recordar mejor el contenido de los sitios web que eran considerados como altamente creíbles en comparación con aquellos que no lo eran (Pareira, 2012). Estos estudios sobre credibilidad de los medios de comunicación sugieren que la percepción de la gente de un medio noticioso o la impresión sobre un determinado medio influye en el procesamiento cognitivo (Ardèvol-Abreu, Hooker y Gil de Zúñiga, 2017).…”
Section: Revisión De La Literaturaunclassified